Development and relative validity of a new field instrument for detection of geriatric cachexia: preliminary analysis in hip fracture patients. Issue 3 (18th May 2013) - Villani, Anthony M.; Miller, Michelle D.; Cameron, Ian D.; Kurrle, Susan; Whitehead, Craig; Crotty, Maria
Abstract : Background: Geriatric cachexia is distinct from other age‐related muscle wasting syndromes; however, detection and therefore treatment is challenging without the availability of valid instruments suitable for application in the clinical setting. This study assessed the sensitivity and specificity of a newly developed screening instrument utilising portable assessments against previously defined and commonly accepted diagnostic criteria for detection of geriatric cachexia. Methods: Cross‐sectional analyses from 71 older adults' post‐surgical fixation for hip fracture were performed. The diagnostic criteria required measures of appendicular skeletal muscle index derived from dual‐energy X‐ray absorptiometry and anorexia assessed by ≤70 % of estimated energy requirements. These assessments were replaced with mid‐upper arm muscle circumference and the Simplified Nutritional Appetite Questionnaire, respectively, to create a field instrument suitable for screening geriatric cachexia. Sensitivity, specificity and positive and negative predictive values were calculated. Results: The current diagnostic algorithm identified few patients as cachectic (4/71; 5.6 %). The sensitivity and specificity of the geriatric cachexia screening tool was 75 and 97 %, respectively. The screening tool had a positive predictive value of 60 % and a negative predictive value of 99 %. Conclusions: Given the unexpected prevalence of cachexia in such a vulnerable group, these results may suggest problems in operationalising of the consensus definition and diagnostic criteria. Although the application of a newly developed screening tool using portable field measures looks promising, the authors recommend additional research to identify the prevalence of geriatric cachexia, which captures all diagnostic criteria from the consensus definition. Future investigation may then be positioned to explore the predictive validity of screening tools using portable field measures, which potentially achieve higher sensitivity.